Corporate Social Responsibility Decision-Making Considering Multiple Factors in a Duopoly Model - He Liang; Xiaomin Sun; Yanli Guo (Amfiteatru Economic)
This study constructs a duopoly model considering corporate social responsibility (CSR), examines the results of different CSR decisions, and analyzes how factors like CSR level, tax rates, externalities, and consumer sensitivity affect results. The findings show that these factors have complex impacts and that the implementation of CSR can create a win-win situation under certain conditions. Firms should consider the CSR actions of their competitors and pay careful attention to taxes, externalities, and consumer sensitivity when making CSR decisions. Implementing CSR benefits firms when CSR levels and tax rates are within a specific range. When consumer sensitivity is high or negative externalities are large, it is conducive to promoting a more active implementation of CSR, thus helping firms obtain higher returns or reduce negative externalities.